Correcting for the Problems of the Survey Course. Issue 1 (5th May 2017) - Shields, Sarah
Abstract : Every year, I teach a broad survey course on the Modern Middle East (between 120 and 200 students), along with seminars on a wide range of topics. Regardless of the content of these courses, I have three big goals. I want them to come away understanding that the history of the region is more complex and fascinating than they learned in high school and from the pundits, and the simplistic assumptions and solutions they offer answer no questions. Second, I want to persuade them that things change over time, and we can't understand anything without knowing its context—and the context of the Middle East is global. But most imperative: I want to convince students to be critical in analyzing sources of information. Informed citizenship requires students to be able to think critically, and that is what historians do offer. We analyze multiple sources in myriad ways.